2014
DOI: 10.1161/circep.113.001340
|View full text |Cite|
|
Sign up to set email alerts
|

Sodium Channelopathy Underlying Familial Sick Sinus Syndrome With Early Onset and Predominantly Male Characteristics

Abstract: Background— Sick sinus syndrome (SSS) is a common arrhythmia often associated with aging or organic heart diseases but may also occur in a familial form with a variable mode of inheritance. Despite the identification of causative genes, including cardiac Na channel ( SCN5A ), the pathogenesis and molecular epidemiology of familial SSS remain undetermined primarily because of its rarity. Methods and Results— … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 28 publications
4
32
2
Order By: Relevance
“…We recently found that familial SSS probands carrying SCN5A mutations showed a significantly earlier disease onset and a strong male predominance, whereas nonfamilial SSS had a disease onset of over 70 years for both sexes, which were affected equally. 22 The affected members of the SSS family in the present study were both women, aged over 60 years, suggesting that familial SSS with MYH6 mutations might constitute an SSS subgroup distinct from that caused by SCN5A mutations. This may suggest the existence of a new disease entity of inherited arrhythmias attributable to mutations in genes encoding sarcomere proteins other than cardiac ion channel or ion channel-associated genes.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…We recently found that familial SSS probands carrying SCN5A mutations showed a significantly earlier disease onset and a strong male predominance, whereas nonfamilial SSS had a disease onset of over 70 years for both sexes, which were affected equally. 22 The affected members of the SSS family in the present study were both women, aged over 60 years, suggesting that familial SSS with MYH6 mutations might constitute an SSS subgroup distinct from that caused by SCN5A mutations. This may suggest the existence of a new disease entity of inherited arrhythmias attributable to mutations in genes encoding sarcomere proteins other than cardiac ion channel or ion channel-associated genes.…”
Section: Discussionmentioning
confidence: 54%
“…22 We found that the mutant delE933-MYH6 slowed down action potential propagation when heterologously expressed in the atrial myocardial cell line HL-1 ( Figure 4A). Moreover, knockdown of endogenous MYH6 leading to reduced heart rate in zebrafish could be compensated for by the coexpression of WT-MYH6 but not by delE933-MYH6 ( Figure 4B).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…11, 12 To date, SCN5A-D1275N has been reportedly associated with a wide variety of arrhythmias, with or without DCM. 13, 25 Functional studies into the electrophysiology of SCN5A-D1275N channels have reported contradictory results. Some studies using heterologous expression systems such as Xenopus oocytes, Chinese hamster ovary cells, or tsA201 cells, showed no major differences in the peak sodium current densities and sodium channel kinetics of WT and D1275N channels, 14,16 whereas another study using Xenopus oocytes and HEK 293 cells found a reduction in peak sodium current densities in D1275N channels.…”
Section: D1275n Hipsc-cms Display Lower Sodium Channel Protein Expresmentioning
confidence: 99%
“…Conduction disturbances in BS have been associated with a worst outcome, 18 and relation between SND, sodium channelopathies, and BS is well known. [19][20][21] The mechanism responsible for this is not clear; a more expressive form of the disease might be involved. Specific studies with biggest population and follow-up should be performed to clarify this issue.…”
Section: Risk Factorsmentioning
confidence: 99%